Melanoma in tanning bed users - Borkowska, Barbara; Kardynał, Agnieszka; Słowińska, Monika; Maj, Małgorzata; Sicińska, Justyna; Czuwara, Joanna; Piekarczyk, Ewa; Szymańska, Elżbieta; Kurzeja, Marta; Warszawik-Hendzel, Olga; Jasińska, Magdalena; Walecka, Irena; et al. (Dermatology Review/Przegląd Dermatologiczny, 2013)
Introduction. Melanoma incidence is increasing worldwide. Numerous scientific studies have documented the relationship between exposure to ultraviolet radiation in solariums, and an increased risk of melanoma and nonmelanoma skin cancer. Objective. Evaluation of the time that passes from intensive use of tanning beds to the diagnosis of melanoma and assessment of the impact of tanning beds on melanoma progression. Material and methods . The study included 212 patients (121 women and 91 men) with melanoma aged 19–90 years and 106 age and sex matched healthy control individuals. Data about the use of tanning beds were obtained from a detailed questionnaire. Other data were obtained from the medical records of the patients. Results . A total of 79/212 (37.2%) patients reported using tanning beds prior to the diagnosis of melanoma, including 23/212 (10.8%) patients using tanning beds 10 or more times in their life. In the healthy control group the corresponding data were 35/106 (33.0%) and 14/106 (13.2%). Among those who used tanning beds, the average number of visits in tanning salons was 28.6 ±38.1 (mean ± standard deviation) in patients suffering from melanoma and 9.1 ±8.9 in healthy subjects (p < 0.05). The average thickness of melanoma according to Breslow score was significantly lower in patients who have used tanning beds compared to those who have never tanned in tanning salons. These values were 2.1 mm and 3.1 mm respectively. Melanoma was diagnosed after an average of 8.8 years from the time of the most intense exposure to tanning beds. Conclusions . Patients with melanoma, who used tanning beds developed the cancer after an average time of 8.8 years. Superficial spreading melanoma was more common in this group compared to patients who were never exposed to artificial UV light in tanning beds.